Determining the impact of roasting degree, coffee to water ratio and brewing method on the sensory characteristics of cold brew Ugandan coffee - Seninde, Denis Richard (Kansas State University, 2018)
In today’s market, there is a growing demand for high-quality coffee with distinctive sensory characteristics. An example of such coffees is the cold brew which has become quite popular. Despite the increasing prevalence of cold drip/brewed coffee, little-published research exists on the factors that impact the sensory characteristics of cold brew coffee. The objectives of this study were to determine the impact of a) degree of roasting, b) coffee to water ratio (C2WR) and c) brewing methods on cold brew coffee from d) Ugandan coffee beans. Four distinct coffee samples, sourced from different lowland and mountainous regions in Uganda, were roasted and tested using a factorial design that allowed comparison of all main factors (a-d) and their interactions. The samples were evaluated by a highly trained sensory panel based on 42 attributes from a previously published coffee lexicon. Results showed that all aspects studied (Ugandan variety, roast degree, C2WR, and brewing method) had an impact on most of the attributes. For example, Robusta coffees generally had a more bitter taste than Arabica coffees and the Dark roast samples generally were more bitter than the Medium roast coffees. In addition, coffee samples that were brewed using a higher coffee to water ratio (C2WR) generally were more bitter than the coffees that were brewed using a lower C2WR. However, although most of the main effects had a significant impact, their effects were mitigated by their interaction with other factors. For example, Medium roast Robusta that was slow-dripped with a high C2WR had a more bitter taste than the corresponding Arabica samples however when the Medium roast Robusta was steeped with a high C2WR it had a similar bitter intensity with the corresponding Arabica samples. Thus, although major impacts are critical, individual sample combinations must be considered when evaluating coffee samples for their impact on the sensory characteristics.
Keywords: Coffee roasting; Brewing methods; Coffee to water ratio; Cold brew; Coffee sensory characteristics; Uganda coffee